-3x+1=-9x+16

Simple and best practice solution for -3x+1=-9x+16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x+1=-9x+16 equation:



-3x+1=-9x+16
We move all terms to the left:
-3x+1-(-9x+16)=0
We get rid of parentheses
-3x+9x-16+1=0
We add all the numbers together, and all the variables
6x-15=0
We move all terms containing x to the left, all other terms to the right
6x=15
x=15/6
x=2+1/2

See similar equations:

| 3x-5/25=10 | | -9-3x=-14-1-7x-2 | | 4/5(x+2)=20 | | 7/8w=183/8 | | 2(2t+4)=3/4(28-8t) | | (2x2)=3 | | 7y-4=8-3y | | 7=-8+1x | | 2x+8=2x+11-3 | | -12x=-18-30 | | 3-2y=-7+8y | | a/2-a3=-30 | | -12x=x/5-7 | | -(x+4)+5x=36 | | 5x+8=3x-88 | | -3x+3=-x+12 | | 14-2u=−12 | | 7x+20=6x+2 | | x+2/4-x-1=2 | | -8k^2=224 | | -r-18=r+4 | | X+5/2=2(x+6) | | 18−6a=4a−4(a+3) | | 2y/5-5=3y+8 | | 6+3x=5(x–1)–3(x-2) | | 3(2x-5)+2x=33 | | -63=14+4x | | x+4+5x=3(2x−1) | | 7(x-8)+9=-6x+5(x+5) | | 3.4h=30.6 | | −2x​ =−10 | | 6(2y=2)=36 |

Equations solver categories